Investigating hepatic fibrosis heterogeneity by three-dimensional imaging in metabolic dysfunction-associated steatotic liver disease - Buket Yigit; Ekin Ozgonul; Omer Yaman; Tarik Sipahioglu; Burge Ulukan; Yagmur Cetin Tas; Berna Morova; Musa Aydin; Yigit Uysalli; Elif Demirtas; Mert Erkan; Gurkan Tellioglu; et al. (Scientific Reports)
Abstract Although liver biopsy is a well-established technique to assess fibrosis it has several limitations, including invasive nature, semi-quantitative assessment methods, significant sampling and observer variability, making precise assessment of hepatic fibrosis challenging. Accurate and reliable modalities are crucial for clinical trials to characterize hepatic fibrosis monitorization effectively. We aimed to perform 3-dimensional imaging of optically transparent liver samples by light-sheet microscopy (LSM) to quantify extracellular matrix (ECM) proteins. Fifty-seven MASLD, thirty-eight chronic hepatitis patients and twelve healthy individuals were included. Liver tissues were cleared with a CLARITY method. 3D imaging of ECM was performed via the newly developed LSM. Collagen Proportionate Volume (CPV) and Elastin Proportionate Volume (EPV) values were calculated by analysis of over 200 sections per sample through morphometry. We have optimized a method which achieves transparency of liver tissues in advanced fibrotic stages of MASLD and optimized non-destructive slide-free fibrosis pathology of whole fresh and FFPE liver biopsy samples. Cut-off values for CPV and EPV were established for fibrotic stages. CPV and EPV analysis showed a considerable optical section heterogeneity resulting in a fibrosis stage of variance within the sample. Volumetric image analysis for fibrosis staging revealed that only 44% and 47% of optical sections would be staged the same for F3 and F4, respectively. For the first time, our findings demonstrate a novel method of analyzing 3D digital pathology of liver fibrosis using in-house LSM. Volumetric imaging of whole liver biopsy samples showed that fibrosis heterogeneity occurs even in different sections.